AN EPIDEMIOLOGICAL STUDY OF HEPATITIS VIRUS DISEASE FOR SOME PATIENTS IN AL_SHATRAH GENERAL HOSPITAL (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
This study was reviewed by relying on the available records of the spread of hepatitis A, B and C in Dhi Qar Province during this year in Al-Shatrah General Hospital. The study included 20 cases of males and females, where the number of males was 13 while the number of females was 7. The comparison was made with the control group, which numbered 8 males and 12 females, this study did not shows  a significant difference between the control group and the patients group when the two groups were divided by sex, where the value of P< 0.05. The current study also recorded a higher prevalence of hepatitis C virus in this region followed by type B and finally type A. Also, the present study shows that most patients were males with type C virus